(untitled) (Revista de Estudos da Linguagem, 2024)
This work, located at the interface of textual studies with Cognitive Linguistics, focuses on the ministerial meeting of the Bolsonaro government (Brazil) that took place on April 22, 2020, focusing on the speech of the then Minister of Education, Abraham Weintraub. The general objective of this investigation is: to analyze how metaphors contribute to the construction of meanings in Abraham Weintraub’s speech. The specific objectives are: a) to identify, classify and map the emerging metaphors and b) to analyze the relationship between the emerging metaphors and the argumentative construction of the text. In order to achieve the established objectives, the constant metaphors in the analyzed text were identified (Dienstbach, 2018), classified into conventional metaphors, conceptual metaphors, situated metaphors, new metaphorical developments and metaphorical niches (Lakoff; Johnson, 2002; Vereza, 2007; 2013), and also mapped (Kövecses, 2002). Among the localized metaphors, the emergence of the metaphor stands out: POLITICS IS WAR/FIGHT. This, when opposed to the metaphor POLITICS IS GAME, gives rise to the unfolding policy is game, but it must be war/fight, a central position defended by the speaker. In order to justify it, Weintraub highlights that the dispute that the group at the meeting is having against its adversaries is being lost and establishes targets against which they must act: Brasília and the Brazilian state.